Assesment Of Management Strategies For Selected Forest Reserves In Ibadan, Oyo State, Nigeria. - T. T., Agbi; L. O., Alamu; A. A., Oladiti (Advances in Social Sciences Research Journal, 2018)
Forests reserve management strategies should provide comprehensive forest working plan for each Forest Reserve, consolidate the existing forest reserves, carry out periodic National Forest Resources inventory, Involve communities in the management of forest reserves with clearly defined roles and responsibilities, promote equitable benefit sharing and designate roles and responsibilities amongst stakeholders, protect the Forest Estate from fire and encroachment, encourage multiple-use concepts in the management of forest reserves. Most of these management strategies are mostly only protected on paper, as the forest continues to be subjected to official and unofficial unsustainable logging, and virtually unrestrained firewood and plant collecting. This study assessed the management strategies for selected forest reserve schemes in Ibadan, Oyo state, Nigeria. The study analyzed the respondents’ socio demographic characteristics, their level of knowledge on the forest reserve management and level of agreement on the identified Government policies for forest reserve maintenance. Forty (40) questionnaire packs were administered on the workers of Onigambari forest reserves (10), Oluyole Local Government Area, Oso forest reserve (5) and Ijaye forest reserve (5), Akinleye Local Government Area, Moniya, the staff and students in the university of Ibadan, department of forest and forest products (4), the neighboring communities around the forests (4) and the staff in the ministry of Agriculture, Natural resources and Rural development, Ibadan (12). Likert scale was used to rank the knowledge level of the respondents, simple descriptive statistics such as frequency mean and percentages was used to describe the socio-demographic characteristics of the respondents. To test the hypothesis, Pearson correlation demographic analysis was used to test the significant relationship between the selected demographic variables and the dependent variables. The result of the findings showed that some of the selected demographic variables such as marital status (r = 0.670**; p < = 0.01), occupation (r = 0.544**; p < =0.01) and years of occupational experience (r = 0.382*; p< 0.05) respectively exhibited a significant relationship with the dependent variable that is perception of level of knowledge on the forest resource management). This implies that all the demographic variables have decisive influence on the dependent variable. Furthermore, the status of management of selected forest reserves in Ibadan was discovered to be inadequate and the stakeholders have proper knowledge of the forest resources management and the policies. There is need for incentives so that stakeholders and other practitioners can adequately use their knowledge to improve on forest management in the study area.